2012
DOI: 10.1007/s00122-012-2030-4
|View full text |Cite|
|
Sign up to set email alerts
|

QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions

Abstract: Heat and drought adaptive quantitative trait loci (QTL) in a spring bread wheat population resulting from the Seri/Babax cross designed to minimize confounding agronomic traits have been identified previously in trials conducted in Mexico. The same population was grown across a wide range of environments where heat and drought stress are naturally experienced including environments in Mexico, West Asia, North Africa (WANA), and South Asia regions. A molecular genetic linkage map including 475 marker loci assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 34 publications
16
58
1
Order By: Relevance
“…Previous studies reported a large number of QTL for several physiological and agronomic traits under different conditions [9][10][11]27,28]. In the present study, we detected QTL for CTa, CTg1, and CTg2 on Chr.…”
Section: Qtl Mappingsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies reported a large number of QTL for several physiological and agronomic traits under different conditions [9][10][11]27,28]. In the present study, we detected QTL for CTa, CTg1, and CTg2 on Chr.…”
Section: Qtl Mappingsupporting
confidence: 66%
“…Physiological traits, as well as PH and TKW, are critical elements of GY. The wide use of molecular markers has made possible the study of quantitative traits [9,11,23] and detect QTL that allow the development of high-yield cultivars via MAS. Previous studies identified numerous QTL associated with yield-related traits in various populations [1,9,10,[19][20][21]27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular markers consisted of 27 AFLP, 6 SSR and 10 DArT Lopes et al 2013). 1B-a was considered as the T1BL/1RS region (for more details see Mathews et al 2008 andMcIntyre et al 2010).…”
Section: Qtl Analysismentioning
confidence: 99%